AKTIFITAS PENGINDERAAN JAUH MELALUI SATELIT DI INDONESIA DAN PENGATURANNYA DALAM HUKUM RUANG ANGKASA - Irma H Hanafi (SASI, 2011)
Remote sensing by satellite can overcome the difficulties of data collection due to the condition of the territory of Indonesia which is still composed of regions that are difficult to achieve, can present data to assess natural resources and environment, as well as monitor ongoing changes either due to natural changes and darmpak of human activity.  Differences of interest between owners of developed countries of remote sensing technology with developing countries as an owner of natural resources which is the object of sensing data obtained from satellites. Differences interests of the countries encourage the creation of differences in perception of the law.  As an activity space, remote sensing by satellite is subject to the provisions of international law governing the activities of states in space.